ANALISIS KASUS PADA USAHA KECIL DAN MENENGAH MS COLLECTION KERAJINAN KAIN PERCA DI KELURAHAN GANDEKAN KECAMATAN JEBRES KOTA SURAKARTA - Ratih Rahmawati; Suparman Jayadi (UNIVERSITAS SEBELAS MARET (UNS), 2019)
Small and medium enterprises (SMEs) program are still not running optimally, for there are few barriers to social disintegration in MS Collection. This research aimed to find case analyze on Patchwork Crafts